Design Of Smart Packaging Machine Liquid Soap Using Pugh’s Method - Mohd Saib, Khairul Anwar; Hassan, Muhammad Zahir; Karjanto, Juffrizal; Md. Yusof, Nidzamuddin; Ab Wahab, Norfariza (World Academy of Research in Science and Engineering, 2020)
Packaging is an important process for the laundry industry. The use of packaging machine technology in developing countries is to minimize production costs that will lead to a better economic development and packaging production. Current conditions in Malaysia, the heat impulse sealer is used for small industries to carry out the packaging business. A project was carried out to provide the design and development of packaging machine, either manually or mechanically. The objective of this project was to create a new concept of producing a packing containing a cleaning fluid using Pugh’s Method. The machine was designed to reduce human effort to pack a cleaning fluid. In order to reduce human effort to operate the machine, a Manual Stamping Filling Sealing (MSFS) machine was designed based on several concept ideas, computer aided drawing software and CATIA V5 was used to design the MSFS machine. The target groups for this project are the household and industrial detergent companies.